2012
DOI: 10.1007/s00402-012-1584-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of femoral head osteonecrosis with advanced cell therapy in sheep

Abstract: Our findings indicate that a BMCSs loaded bone matrix scaffold is capable of stimulating bone regeneration more effectively than isolated core decompression or in association with an acellular scaffold in a preclinical femoral head osteonecrosis model in sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Osteoblasts, common in the growth of bone tissue, gather in the newly formed bone surface, and have an important role in the process of bone tissue development, bone metabolism and bone mass balance maintenance and damage repair (7)(8)(9). Femoral head necrosis is a common intractable clinical orthopedic disease, and previous studies found that it may be closely associated with the dysfunction of osteoblasts and bone marrow stromal cells (10)(11)(12). The mechanism is that bone marrow stromal cells differentiate into adipocytes, and hormones regulate bone marrow stem cell differentiation into fat cells.…”
Section: Discussionmentioning
confidence: 98%
“…Osteoblasts, common in the growth of bone tissue, gather in the newly formed bone surface, and have an important role in the process of bone tissue development, bone metabolism and bone mass balance maintenance and damage repair (7)(8)(9). Femoral head necrosis is a common intractable clinical orthopedic disease, and previous studies found that it may be closely associated with the dysfunction of osteoblasts and bone marrow stromal cells (10)(11)(12). The mechanism is that bone marrow stromal cells differentiate into adipocytes, and hormones regulate bone marrow stem cell differentiation into fat cells.…”
Section: Discussionmentioning
confidence: 98%
“…[23][24][25] Furthermore, quite a number studies have manifested that transplanted autologous or allogeneic MSCs were capable of survival, proliferation, and differentiation into osteoblasts directly in the necrotic femoral head on humans 26-28 and a variety of animal models; for example, in mouse, 29 rabbit, 30,31 dog, 32 and sheep. 33 Thus, regulation on the osteogenesis and adipogenesis of MSCs is the novel therapeutics for ONFH treatment. Therefore, we explored the molecular mechanism by which HG impacts the function of ONFH during MSC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only because of the multilineage progenitor potential of MSCs, but also because of their capacity to modulate the host microenvironment by secreting a variety of factors, such as cytokines, chemokines or growth factors, which can mediate diverse functions via crosstalk between different cell types (Friedenstein et al, ; Doorn et al, ; Murphy et al, ). Examples of using sheep as a model system include spinal fusion (Goldschlager et al, ), segmental tibial defects (Niemeyer et al, ), chondral/osteochondral repair (Ahern et al, ; Caminal et al, ,b, ; Vives et al, ), tendon and ligament regeneration (Lacitignola et al, ) and osteonecrosis of the femoral head (Velez et al, ), among others.…”
Section: Introductionmentioning
confidence: 99%